Managing risk in developing countries : national demands and multinational response - Samuels, Barbara C., 1954- (Princeton legacy library, 1990)
In light of the increasing global competition among both multinational companies and national economies, Barbara Samuels examines a source of economic tension that has broad social implications: as multinational companies (MNCs) strive for cheaper labor and new markets, less-developed countries (LDCs) are becoming more concerned with extracting benefits from these companies to achieve their development objectives. Samuels centers her study on the variables shaping the responses of MNCs to national demands while considering current debates on country risk, global competitiveness, and national industrial policy. Advancing a micro-view of the MNC and its host country in two case studies, Samuels shows how an MNC subsidiary's integration with headquarters and its closeness with local government affect its management of risk and its ability to deal with LDC demands. Here the author investigates the labor and investment policy changes brought about when various automotive subsidiaries interacted with national interest groups in Brazil and with the government in Mexico. Both cases illustrate how the policy response of one subsidiary creates the dynamics for defensive policy changes of its competitors. MNC managers and LDC policymakers can draw important conclusions. Originally published in 1990. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.